2017
DOI: 10.1016/j.jcrc.2017.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Heated humidified high-flow nasal cannula oxygen after thoracic surgery — A randomized prospective clinical pilot trial

Abstract: Background Thoracic surgery patients are at high-risk for adverse pulmonary outcomes. Heated humidified high-flow nasal cannula oxygen (HHFNC O2) may decrease such events. We hypothesized that patients randomized to prophylactic HHFNC O2 would develop fewer pulmonary complications compared to conventional O2 therapy. Methods and Patients Fifty-one patients were randomized to HHFNC O2 vs. conventional O2. The primary outcome was a composite of postoperative pulmonary complications. Secondary outcomes included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Firstly, only 4 trials are analyzed and sample is not too large in 2 trials (n < 110). [ 33 , 34 ] The ratio of sample between experimental group and control group in 2 trials is close to 1:1, and the design of control group is reasonable. The weight of these 2 studies is important in the meta-analysis.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Firstly, only 4 trials are analyzed and sample is not too large in 2 trials (n < 110). [ 33 , 34 ] The ratio of sample between experimental group and control group in 2 trials is close to 1:1, and the design of control group is reasonable. The weight of these 2 studies is important in the meta-analysis.…”
Section: Discussionmentioning
confidence: 86%
“…Two studies reported pulmonary complications, [ 33 , 34 ] such as atelectasis, suspected pneumonia, hypoxemia, and hypercapnia. There was significant difference in pulmonary complications between 2 groups (OR = 0.28, 95% CI = 0.13−0.6, P = .001, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ten trials [51][52][53][54][55][56][57][58][59][60] compared prophylactic HFNC to COT and only one trial compared HFNC to NIPPV [61]. Of these, six trials were conducted in patients following cardiac surgery [53,55,57,58], four trials were conducted following thoracic surgery [51,52,56], and one trial was performed in patients after major combined thoracic and abdominal surgery [54]. With the exception of blinding, all trials, except one [52], were judged to be at low or probably low risk of bias.…”
Section: Evidence Summarymentioning
confidence: 99%
“…Of these, six trials were conducted in patients following cardiac surgery [53,55,57,58], four trials were conducted following thoracic surgery [51,52,56], and one trial was performed in patients after major combined thoracic and abdominal surgery [54]. With the exception of blinding, all trials, except one [52], were judged to be at low or probably low risk of bias. One trial was judged to be at high risk of bias as it did not adhere to an intention-totreat analysis.…”
Section: Evidence Summarymentioning
confidence: 99%
“…Finally, 8 articles met our inclusion criteria and were selected for data extraction, analysis, and quality assessment. [16][17][18][19][20][21][22][23] A flow chart of the search strategy and the reasons for exclusion are shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%